PENGEMBANGAN MODEL PEMBELAJARAN NON DIREKTIF - BERBASIS MASALAH UNTUK MENINGKATKAN KEMANDIRIAN BELAJARMAHASISWA - BACHRI, Bachtiar Sjaiful (2010)
Education on the 21st century is the development of intelligence, that pupils can help themselves with the intelligence they have. Tan (2003:1) explained : "Developing intelligences is about learning to solve problems. Problem solving in real world contexts involves multiple ways of knowing and learning". Individual ability to keep developing through independence in learning would really determine the competition that pupils have in the global era. It means that independent learning is the condition needed that pupils are able to have navigation in determining various activities to reach the goal.Such condition is needed by university students for their learning process. Since the education needs accomodated by the curriculum do not merely demand the pursuit of academic master (curriculum as a race course of subject matters to be mastered; Zais), but also demanding the pursuit of ability to master the root of continuous learning which can be determined through independent learning (curriculum is all experiences which are offer to learner under the auspices or direction of the school; Caswell). So that the curriculum implemented in learning activities can accomodate the whole learning needs as curriculum concept: The plan or program for all experiences which the learner encounters under the direction of the school (Olivia, 1982 ).Research methodology used is the research methodology and development or " Research and Development", Borg and Gall (1989) are devided into 3 big stages, as stated in details : Stage 1 is preface study, Stage 2 The development to complete models in class activities, Stage 3 Models test through quasi experiment to find out the internal and external effectivities in model implementation.Referring to the research question, the conclusion of this research is : 1) Studying model result is nondirective learning model - based on problems, 2)Model result covering 4 phases : a) Orientation phase, facilitating university students as the study subjects to express themselves in letting out their study needs, b) Exploration phase, in this phase the students explore their independence to solve problems, c) Conclusion phase, this phase consists of 2 phases which are students doing analysis and evaluating the process of solving problems, d) Reflexion/initiation phase, is the last/ final phase which emphasize on the value and attitude of independent study. The implication of research results, among others: 1) Studying model which is developed can improve the studying independence, as well as improving study achievement, 2) Studying model which is developed, is based on the humanism approach which position the students as the study subjects, in order to give the students freedom in digging and enlarge the individual understanding in fulfilling the needs of studying.